Effects of Obesity on Blood Pressure Among Adult Malesand Females in Tikrit City - Sep-Dec, 2008 - Q Hamdi, Anas; K Asaad, Nahla; K Asaad, Asef (Tikrit Journal of Pharmaceutical Sciences, 2023)
Obesity is an independent risk factor for cardiovascular disease. Clinical studies have shown that body weight reduction decreases blood pressure. The aim of this study was to illustrate the relationship between obesity and blood pressure among adult males and females in Tikrit city. A case series study among the population aged over 25, (400 individuals, 200 males and 200 females) in Tikrit city. Sample was collected from September till December 2008. The blood pressure of subjects was measured in three occasions one month apart via mercurial sphygmomanometer by well trained personnel to those patients attending to Medicine outpatient of Tikrit Teaching Hospital. Mean systolic blood pressure (SBP) was significantly lower in all groups (P<0.005) in non-obese compared with obese patients. This positive relation well indicates the higher the BMI, the more elevated SBP. However, reduction of diastolic blood pressure (DBP) mean was significant only in men and women who were under treatment with antihypeftensive drugs (P<0.05). In all hypertensive groups and in healthy subjects, there was an increase in body mass index (BMI). This increase was more notable in hyper-tensive groups, compared with healthy individuals. The prevalence of obesity in hypertensive patients was higher than that of the healthy group.